Titrimetric Analysis of Chloride Concentration in Beers using Synthetic Mercury(II) Compound - Labhade, S.R.; Labhade, K.R. (Asian Journal of Chemistry, 2021)
The monothiocyanato-mercuric(II) nitrate [Hg(SCN)NO3] reagent has been prepared synthetically in an aqueous medium and subjected for studies of titrimetric analysis of chloride concentration in beers. In this studies, a measured volume of beer sample was added into known and an excess amount of Hg(SCN)NO3 reagent and the surplus Hg(SCN)NO3 was determined by back titration against standard potassium thiocyanate (KSCN) solution using ferric nitrate [Fe(NO3)3] indicator. The chloride ion and Hg(SCN)NO3 were found to be reacting in the 1:1 stoichiometric ratio. The amount of chloride in beer was determined with the amount of Hg(SCN)NO3 utilized in the titration reaction. The presence of organic and inorganic materials had no effect on the titrimetric assay of chloride concentration in beers as proved by the chloride recovery experiment. The statistical analysis of results showed average standard deviation of 0.01034 and average relative error 1.12%, which indicates the accuracy of the procedure.